Dicer1 Promotes Colon Cancer Cell Invasion and Migration Through Modulation of tRF-20-MEJB5Y13 Expression Under Hypoxia - Luan, Na; Mu, Yali; Mu, Jiayi; Chen, Yiquan; Ye, Xun; Zhou, Qin; Xu, Miaorong; Deng, Qun; Hu, Yeting; Tang, Zhe; Wang, Jianwei (Frontiers in Genetics, 2021)
Hypoxia plays a key role in colorectal cancer (CRC) metastasis, but its underlying mechanism remains largely unknown. Dicer1, an RNase, has been considered as a tumor regulator in many tumors. However, whether Dicer1 affects CRC progression under hypoxia remains uncertain. In this study, we found that Dicer1 expression was induced by hypoxia in CRC cells and it mediates hypoxia-induced CRC cell progression. Furthermore, we found that the expression of tRF-20-MEJB5Y13, a small non-coding RNA derived from tRNA, was increased under hypoxic conditions, and its upregulation by Dicer1 resulted in hypoxia-induced CRC cell invasion and migration. These results advance the current understanding of the role of Dicer1 in regulating hypoxia signals and provide a new pathway for the development of therapeutic interventions for inhibiting cancer progression.